2022
DOI: 10.1186/s13019-022-02034-y
|View full text |Cite
|
Sign up to set email alerts
|

The perioperative outcomes of uniport versus two-port and three-port video-assisted thoracoscopic surgery in lung cancer: a systematic review and meta-analysis

Abstract: Background Uniport video-assisted thoracoscopic surgery (VATS) has been applied widely for the treatment of lung cancer in recent years. Some studies have reported that uniport VATS might provide better outcomes than multiport VATS. However, the perioperative outcomes of uniport VATS compared with two-port and three-port VATS, respectively, have yet to be studied at a comprehensive scale. This meta-analysis study compares the perioperative efficacy among uniport, two-port, and three-port VATS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…The treatment of CAP patients is extremely challenging and requires a multidisciplinary team of specialists, including respiratory physicians, interventionalists, and thoracic surgeons.According to the ndings of earlier investigations, bronchial arterial embolism can prevent life-threatening hemoptysis [26][27][28] .The European Respiratory Society's clinical recommendations for the diagnosis and treatment of pulmonary aspergilloma also suggest preoperative bronchial arterial embolism as an effective treatment method for life-threatening hemoptysis 5 .In our study,preoperative bronchial arterial embolism was conducted in 12(10.9%) hemoptysis patients, and two cases of them experienced recurrent hemoptysis before lung resections. Neither pharmacological nor bronchial artery interventions can cure pulmonary cavities in CAP patients, and they cannot prevent massive hemoptysis due to hyperplasia of vessel in the chest wall or para bronchus, so CPA patients often require surgery to block the proliferating trophoblastic vessels and remove the destroyed lung parenchyma.In CPA patients, dense adhesions are often formed between the diseased lung lobes and the pleura, and there is a large number of new trophoblastic vessels in the adhesions, so it is the key procedure to separate the adhesions between the diseased lung and the pleura and deal with the large number of trophoblastic vessels within the adhesions in the operation.Current studies show that minimally invasive thoracoscopic surgery might be superior to open chest surgery because of the advantages provided in terms of less pain, fewer complications, a smaller incision, and shorter hospitalization 29,30 .With the development of minimally invasive surgery, many studies have con rmed the effectiveness of thoracoscopy in CPA patients 12,31 .According to the current study, Uni-VATS is gaining popularity and is commonly used in thoracic diseases 32,33 ,but it is rarely used in CPA.According to the literature, Uni-VATS can reduce postoperative pain and facilitate recovery by con ning surgical trauma to one intercostal space 34,35 .In addition, during traditional open chest surgery, the view between the upper lung and the pleural apex is narrower, whereas Uni-VATS allows visual access to the pleural apex and provides advantage in the view of pleural apex area. Therefore, we reviewed CPA patients who had undergone surgery in the last four years and met the criteria at our institution.…”
Section: Discussionmentioning
confidence: 87%
“…The treatment of CAP patients is extremely challenging and requires a multidisciplinary team of specialists, including respiratory physicians, interventionalists, and thoracic surgeons.According to the ndings of earlier investigations, bronchial arterial embolism can prevent life-threatening hemoptysis [26][27][28] .The European Respiratory Society's clinical recommendations for the diagnosis and treatment of pulmonary aspergilloma also suggest preoperative bronchial arterial embolism as an effective treatment method for life-threatening hemoptysis 5 .In our study,preoperative bronchial arterial embolism was conducted in 12(10.9%) hemoptysis patients, and two cases of them experienced recurrent hemoptysis before lung resections. Neither pharmacological nor bronchial artery interventions can cure pulmonary cavities in CAP patients, and they cannot prevent massive hemoptysis due to hyperplasia of vessel in the chest wall or para bronchus, so CPA patients often require surgery to block the proliferating trophoblastic vessels and remove the destroyed lung parenchyma.In CPA patients, dense adhesions are often formed between the diseased lung lobes and the pleura, and there is a large number of new trophoblastic vessels in the adhesions, so it is the key procedure to separate the adhesions between the diseased lung and the pleura and deal with the large number of trophoblastic vessels within the adhesions in the operation.Current studies show that minimally invasive thoracoscopic surgery might be superior to open chest surgery because of the advantages provided in terms of less pain, fewer complications, a smaller incision, and shorter hospitalization 29,30 .With the development of minimally invasive surgery, many studies have con rmed the effectiveness of thoracoscopy in CPA patients 12,31 .According to the current study, Uni-VATS is gaining popularity and is commonly used in thoracic diseases 32,33 ,but it is rarely used in CPA.According to the literature, Uni-VATS can reduce postoperative pain and facilitate recovery by con ning surgical trauma to one intercostal space 34,35 .In addition, during traditional open chest surgery, the view between the upper lung and the pleural apex is narrower, whereas Uni-VATS allows visual access to the pleural apex and provides advantage in the view of pleural apex area. Therefore, we reviewed CPA patients who had undergone surgery in the last four years and met the criteria at our institution.…”
Section: Discussionmentioning
confidence: 87%
“…Cheng et al . [ 5 ] reported that uniport thoracoscopic surgery was associated with less bleeding, shorter duration of postoperative drainage, shorter length of hospital stay, and lower visual analog pain scores on Days 1 and 3 postoperatively compared with the use of two or more ports.…”
Section: Discussionmentioning
confidence: 99%
“…O procedimento padrão envolve o uso de dois locais portais, ou seja, uma incisão principal de 3 a 5 cm e uma incisão de cerca de 1cm para inserção da câmera. Contudo, existem técnicas que utilizam de uma até três locais portais [29].…”
Section: Cirurgia Torácica Vídeo-assistida (Vats)unclassified